2020
DOI: 10.3390/cells9122662
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Analysis of Gliogenesis in the Cerebral Cortex Reveals Stochastic Expansion of Glia and Cell Autonomous Responses to Egfr Dosage

Abstract: Development of the nervous system undergoes important transitions, including one from neurogenesis to gliogenesis which occurs late during embryonic gestation. Here we report on clonal analysis of gliogenesis in mice using Mosaic Analysis with Double Markers (MADM) with quantitative and computational methods. Results reveal that developmental gliogenesis in the cerebral cortex occurs in a fraction of earlier neurogenic clones, accelerating around E16.5, and giving rise to both astrocytes and oligodendrocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…We reported uniform clones composed of either astrocytes, oligodendrocytes, or NG2glia. These results match with previous studies using StarTrack and Mosaic Analysis with Double Markers (MADM) from embryonic progenitors that showed clones composed exclusively of astrocytes [30,45], oligodendrocytes [38], or NG2-glia [31]. However, other studies with MADM did not report any cortical clones containing exclusively oligodendrocytes [45], because RGCs generate diverse cell fate ratios during different embryonic temporal windows.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We reported uniform clones composed of either astrocytes, oligodendrocytes, or NG2glia. These results match with previous studies using StarTrack and Mosaic Analysis with Double Markers (MADM) from embryonic progenitors that showed clones composed exclusively of astrocytes [30,45], oligodendrocytes [38], or NG2-glia [31]. However, other studies with MADM did not report any cortical clones containing exclusively oligodendrocytes [45], because RGCs generate diverse cell fate ratios during different embryonic temporal windows.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, although it is known how cortical progenitors give rise to neurons and some macroglial cell types, the clonal relationships between glial cell types remain partially unknown. Some studies have focused on clonal aspects of astrocyte generation [30,38,[42][43][44][45][46][47][48] and few of them have focused on oligodendrocytes [38,48,49] or NG2-glia [47]. Recent single-cell analysis revealed that glial cells in different layers exhibit distinct transcriptional profiles [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…MADM-11 mice (The Jackson Laboratory, Bar Harbor, USA; #013751, #013749) were crossed to Nestin-cre mice (bred from MADM-11 mice) using the breeding scheme described previously [11] and harvested at the age of one month under the regulations and approval from the Institutional Animal Care and Use Committee at North Carolina State University. Mice were…”
Section: Data Generationmentioning
confidence: 99%
“…MADM allows for simultaneous labeling and genetic manipulation in developmentally derived clones of somatic cells [6]. We and others have extensively used MADM alleles in developmental studies on the roles of various genetic factors, which are involved with neurogenesis [7][8][9] and gliogenesis [10,11]. An advantage of MADM is that neurons and glia with distinct genotypes are permanently labeled by expression of two fluorescent proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from neurogenesis to gliogenesis is one of the key events during brain development, and several molecular signaling pathways regulating this process have been identified, such as janus kinase signal transducer and activator of transcription (JAK-STAT), phosphatidylinositol-3 kinase (PI3K), Notch, and Smad pathways [ 38 , 39 , 40 , 41 ], while extrinsic signals required for induction of astrocytic genes include epidermal growth factor, bone morphogenetic proteins, leukemia inhibitory factor, and ciliary neurotrophic factor (CNTF) [ 42 , 43 , 44 , 45 , 46 ]. In cultures of single neural progenitor cells, transition was associated with activation of chicken ovalbumin upstream promoter transcription factors I and II (COUP-TFI/II) [ 47 ].…”
Section: Astrocyte Development In Cerebral Cortexmentioning
confidence: 99%